The Use of EGRA Technique in Teaching Passive Voice for EFL Classroom - Zaenap, Siti (VELES Voices of English Language Education Society, 2019)
This study aimed at investigating the effectiveness of experience, generalization, reinforcement, and application (EGRA) technique in teaching passive voice of EFL learners. The design of this study was pre-experimental research with pre-test and post-test design. It was conducted at the EFL students of Hamzanwadi University especially in the second semester of English department in the academic year 2017-2018. The sample consisted of 28 students. In determining the sample, this study used cluster random sampling technique. The instrument was objective test in form of multiple choices in order to collect the data. The data was analyzed by using descriptive statistic and paired sample t-test in order to test the hypothesis. The result of descriptive statistic indicated EGRA technique is effective for EFL learners on which the mean score of post-test (14.21) was greater than the mean score of pre-test (9.96). For the hypothesis testing by using paired sample t-test at significance (2 tailed) value level of analyzed data was .000, it was lower than 0.05. So, it indicated that the alternative hypothesis of this study was accepted. In other word, EGRA technique was significantly effective in enhancing students’ ability in passive voice at the second semester of Hamzanwadi University in the academic year 2017-2018.